A polycrystalline diamond micro‐detector for X‐ray absorption fine‐structure measurements. (16th February 2022) - Yao, Lei; Liu, Yunpeng; Wang, Bingjie; Qian, Lixiong; Xing, Xueqing; Mo, Guang; Chen, Zhongjun; Wu, Zhonghua
Abstract : A polycrystalline diamond detector for XAFS measurement has been fabricated. Its volume is 2947 times smaller than a routine ion‐chamber. Abstract : The microminiaturization of detectors used to record the intensity of X‐ray beams is very favorable for combined X‐ray experimental techniques. In this paper, chemical‐vapor‐deposited (CVD) polycrystalline diamond film was used to fabricate a micro‐detector owing to its well controlled size, good thermostability, and appropriate conductivity. The preparation process and the main components of the CVD diamond micro‐detector are described. The external dimensions of the packaged CVD diamond micro‐detector are 15 mm × 7.8 mm × 5.8 mm. To demonstrate the performance of the detector, K ‐edge X‐ray absorption fine‐structure (XAFS) spectra of Cr, Fe, Cu, and Se foils were collected using the CVD diamond micro‐detector and routine ion chamber. These XAFS measurements were performed at beamline 1W2B of Beijing Synchrotron Radiation Facility, covering an energy range from 5.5 to 13.5 keV. By comparison, it can be seen that the CVD diamond micro‐detector shows a more excellent performance than the routine ion‐chamber in recording these XAFS spectra. The successful application of the CVD diamond micro‐detector in XAFS measurements shows its feasibility in recording X‐ray intensity.